Viscous Flow Environments in Oceans and Inland Waters - Publisher, Cambridge Scholars (Cambridge Scholars Publishing, 2019)
This text targets advanced undergraduate students, graduate students and practicing aquatic scientists who seek to understand effects of flow on aquatic processes but have had little prior exposure to fluid dynamics. It provides a self-contained introduction to flows at small scales within oceans and fresh waters in ubiquitous settings, such as boundary layers and dissipative vortices, wherein viscosity suppresses inertial forces. Diagrams, graphs and equations enable reader calculations of viscous flow effects. Detailed derivations include drag forces, solute fluxes and particle encounter rat.